Analisis Manajemen Kesiswaan dalam Meningkatkan Prestasi Akademik dan Non Akademik di SMP Negeri 1 Banyuglugur Situbondo - Nurul Alifah (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2023)
Students are a vital component of educational institutions. Each student possesses diverse abilities, making it necessary to provide them with suitable services and teaching methods to help them achieve their potential. Without effective management, students may not be able to reach their full potential. Therefore, it is essential to have effective student management to efficiently oversee all activities related to students and achieve educational objectives.In light of this, the researcher intends to conduct a study with the following objectives: (1) To understand the planning of student development to enhance both academic and non-academic achievements at SMP Negeri 1 Banyuglugur. (2) To comprehend the implementation of student development activities aimed at improving academic and non-academic achievements at SMP Negeri 1 Banyuglugur. (3) To evaluate the execution of student development programs to enhance academic and non-academic achievements at SMP Negeri 1 Banyuglugur Situbondo.This research employs a qualitative approach, enabling the researcher to observe on-site situations in line with the research questions. Data is collected through observations, interviews, and documentation. Data analysis techniques involve data reduction, data presentation, and drawing conclusions.The study's findings can be summarized as follows: (1) Student development planning involves initial-year meetings where various preparations are discussed to support the smooth execution of academic and non-academic activities, ranging from student admissions to graduation. Additionally, expert mentors are assigned to guide students in achieving excellence in both academic and non-academic aspects. (2) Implementation of student development activities: In the academic sphere, these activities occur daily and include identifying students' potential and capabilities, conducting selections, providing motivation, and allocating additional time for development. In contrast, non-academic activities are conducted outside regular class hours, primarily on Fridays. This includes student outreach and selection through various types of tests, admissions, and the creation of special classes tailored to students' interests and talents. (3) Evaluation of student development: In the academic realm, evaluations are conducted every half-semester by subject teachers. In the non-academic domain, evaluations occur once per semester. Evaluation methods include assessing development outcomes, such as practical tests and comparing targets to achievements, as well as involving students in various competitions like competitions.